2019
DOI: 10.3390/insects10040100
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Stored Product Insect Movements on Integrated Pest Management Decisions

Abstract: Insect movement inside and outside grain bulks and processed products influences pest management decisions. Movement allows insects to find essential food resources, shelters (refuges), warmer and/or humid locations, mating and egg-laying sites, even when they are rare in fields, buildings, mills, warehouses, and inside grain masses. This review discussed the advantages and disadvantages of stored product insect movements, and the influence of insect mobility on some integrated pest management practices. Insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 131 publications
0
24
0
1
Order By: Relevance
“…Insects are attracted to favorable food sources, but also select alternate food sources at the same time (27) . A study by (28) reported the highest rate of progeny production in R. dominica reared on triticale, a hybrid of wheat and rye. The reason why R. dominica preferred wheat grain is that wheat contains nutrients needed for the normal growth, development, reproduction and fitness of the beetle.…”
Section: Discussionmentioning
confidence: 99%
“…Insects are attracted to favorable food sources, but also select alternate food sources at the same time (27) . A study by (28) reported the highest rate of progeny production in R. dominica reared on triticale, a hybrid of wheat and rye. The reason why R. dominica preferred wheat grain is that wheat contains nutrients needed for the normal growth, development, reproduction and fitness of the beetle.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of adult mortality was calculated by counting the number of dead weevils and number of introducing weevils. Based on Jian’s 17 method, the weevils mortality can be calculated by the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…With these abundant stimuli permeating the space around a food facility, it is still unknown from how far insects will be attracted to a location, or how frequently they are, but it is quite clear that some species disperse on the order of multiple to many kilometers, 100 and likely frequently 101 . While recent research has shown that walking insects can only respond to attractants from within a very short distance, 102 it is expected this may be farther for insects orienting while flying during long‐range dispersal 79 . In addition, surrounding a food facility, there may also be hosts or field crop production in the environment that emit attractive volatiles and act as refugia for dispersing insects (Fig.…”
Section: Potential Concerns About Use Of Attractants and Their Mitigation At Food Facilitiesmentioning
confidence: 99%